2022
DOI: 10.1109/access.2022.3164075
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Tracking Assistive Technologies for Individuals With Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis, also known as ALS, is a progressive nervous system disorder that affects nerve cells in the brain and spinal cord, resulting in the loss of muscle control. For individuals with ALS, where mobility is limited to the movement of the eyes, the use of eye-tracking-based applications can be applied to achieve some basic tasks with certain digital interfaces. This paper presents a review of existing eye-tracking software and hardware through which eye-tracking their application is sket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 128 publications
0
24
0
Order By: Relevance
“…Several autonomous and semi-autonomous eyetracking control schemes have been proposed [14], [15], [55]. However, the accuracy of eye-tracking may decreaser for certain eye-types and/or because of disturbances caused glasses or contact lenses [56]. Furthermore, while eye-tracking can provide the system with a directional pointer, it lacks the possibility of providing a go command (similar to a computermouse without any buttons).…”
Section: A Single-modality Control Interfacesmentioning
confidence: 99%
“…Several autonomous and semi-autonomous eyetracking control schemes have been proposed [14], [15], [55]. However, the accuracy of eye-tracking may decreaser for certain eye-types and/or because of disturbances caused glasses or contact lenses [56]. Furthermore, while eye-tracking can provide the system with a directional pointer, it lacks the possibility of providing a go command (similar to a computermouse without any buttons).…”
Section: A Single-modality Control Interfacesmentioning
confidence: 99%
“…Similarly, a haptic AT was developed for the visually impaired considering Braille reading, tactile graphics, orientation, and mobility [31]. Other related efforts were studied in Gaussian hidden Markov model [32], locomotion recognition algorithm [33], three-dimensional (3D)-printed multifunctional hand device (3DP-MFHD) [34], eye-tracking assistive [35], unsupervised sim-to-real adaptation [36]. The major gap is that most works lack details on the effect of angle positioning on distance while keeping the energy absorbed constant.…”
Section: A Efforts On Assisted Living Systemsmentioning
confidence: 99%
“…R ECENT advances in technology have enabled a synergy between wireless technology and healthcare providing accessibility benefits beyond the limitation of the traditional healthcare systems, such as enhanced quality support in medical services and agile response for medical intervention [1]- [3]. Specifically, the Internet of Things (IoT) is simplifying the way the parameters and variables are captured in realtime.…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging the IoT in healthcare can have a significant impact on early diagnosis and intervention in some terminal illnesses, such as heart diseases, and decrease the mortality rate [8]. Eysenbach et al [9] indicated that the telemedicine helped reduce the number of in-hospital admissions of the patients with diseases related to lungs, heart and stroke; hence a considerable decrease in mortality [3]. According to Ebrahimi et al [10], cardiovascular disease (CVD) is the principal reason for human death, answerable for 31 % of the deaths in 2016, at least, about 17.9 million people died from heart disease in 2016, a 31 % of all global deaths.…”
Section: Introductionmentioning
confidence: 99%